How to Interpret Covid-19 Predictions - S. Andrew Schroeder (Philosophy of Medicine, 2021)
The IHME Covid-19 prediction model has been one of the most influential Covid models in the United States. Early on, it received heavy criticism for understating the extent of the epidemic. I argue that this criticism was based on a misunderstanding of the model. The model was best interpreted not as attempting to forecast the actual course of the epidemic. Rather, it was attempting to make a conditional projection: telling us how the epidemic would unfold, given certain assumptions. This misunderstanding of the IHME’s model prevented the public from seeing how dire the model’s projections actually were.